2013
DOI: 10.1038/jid.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes Strain Populations in the Human Skin Microbiome Associated with Acne

Abstract: The human skin microbiome plays important roles in skin health and disease. However, bacterial population structure and diversity at the strain level is poorly understood. We compared the skin microbiome at the strain level and genome level of Propionibacterium acnes, a dominant skin commensal, between 49 acne patients and 52 healthy individuals by sampling the pilosebaceous units on their noses. Metagenomic analysis demonstrated that while the relative abundances of P. acnes were similar, the strain populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
809
3
18

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 599 publications
(891 citation statements)
references
References 44 publications
30
809
3
18
Order By: Relevance
“…In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52. Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52. Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies.…”
Section: Resultsmentioning
confidence: 56%
“…Three (3) were case–control studies and two (2) were small single‐centre, controlled studies, of whom one was a double‐blind, randomized‐controlled trial. In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…They are a reservoir of diversity-generating elements (Rohwer and Thurber, 2009) and regulate both the abundance and diversity of their bacterial hosts by predation (Suttle et al, 1990;Waterbury and Valois, 1993;Rohwer, 2003;Rodriguez-Valera et al, 2009). Although the skin bacterial community has been studied by several groups (Gao et al, 2007;Costello et al, 2009;Grice et al, 2009;Kong et al, 2012;The Human Microbiome Project Consortium, 2012;Blaser et al, 2013;Fitz-Gibbon et al, 2013;Nakatsuji et al, 2013), relatively few studies have characterized the skin viral community (Foulongne et al, 2012;Ma et al, 2014;Wylie et al, 2014). In particular, the composition and dynamics of bacteriophages and their interactions with bacterial hosts on the skin are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The microbial community in the skin pilosebaceous unit is dominated by Propionibacterium acnes, which accounts for nearly 90% of the microbiota (Fitz-Gibbon et al, 2013). Although P. acnes is a major skin commensal, it has been considered a pathogenic factor for acne vulgaris (Leyden, 2001;Bojar and Holland, 2004), one of the most common skin diseases affecting over 80% of adolescents and young adults (White, 1998;Bergler-Czop and Brzezińska-Wcisło, 2013).…”
Section: Introductionmentioning
confidence: 99%